Dynamics of use and abuse of water: a critical appraisal - Sharma, Subhash; Mishra, Devendra (2008)
Here we point out various aspects of water issue. first, we depict the general global and Indian Water Scenarios. Second, we analyse the status of ground water in India. third, we analyse the water availability and pollution of rivers in India. Fourth, we discuss about the commodification of water. Finally, we make some concluding remarks for policy implications from eco-humanistic viewpoint of water as a social need. - Reproduced.
Keywords: Water